Remaining Service Life Discharge Conveyor E pada Tambang Batubara PT XYZ di Kabupaten Merangin Provinsi Jambi - Muhammad Fu'ad; Elfida Moralista; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. The Conveyor is a tool to move material from one place to another efficiently. Conveyor structures are made of steel that is subject to corrosion caused by certain conditions such as environmental conditions. Corrosion can cause thickness reduction and reduce the remaining life of the Conveyor structure. In this study, the Conveyor structure consists of 3 segments with a total of 27 Test points along 114 meters. This study aims to determine the type of corrosion, corrosion control, Corrosion Rate, and Remaining Service Life of the Conveyor structure. The research methodology used is to measure the thickness reduction on the Conveyor structure with the Ultrasonic Thickness Gauge TT 130. This research area has environmental conditions, namely air temperature around 26,7OC – 28,4OC, rainfall around 56,50 mm – 482,80 mm, and the highest relative humidity is 89,3%. The type of corrosion that occurs in the Conveyor structure is uniform corrosion. The corrosion control method uses a Coating method with a Thre layer system. The Coating method for Primer Coating uses Seaguard 5000, Intermediate Coating uses Sherglass FF, and Top Coating uses aliphatic acrylic modified polyurethane. Conveyor structure Corrosion Rate ranges from 0,19 - 0,34 mm/year and based on the relative corrosion resistance of steel is included in the good category. The service life of the Conveyor structure is 7 years and the Remaining Service Life is between 6,41 – 8,89 years. So that there are 48% of Test points that are not reach the design life of 15 years. Keywords: Conveyor Structure, Carbon Steel, Coating, Corrosion Rate, Remaining Service Life Abstrak. Conveyor merupakan alat untuk memindahkan suatu material dari satu tempat ke tempat lainnya secara efisien. Struktur Conveyor terbuat dari bahan baja yang rawan mengalami korosi yang disebabkan oleh kondisi lingkungan sekitar. Korosi dapat menyebabkan pengurangan ketebalan dan mengurangi sisa umur pakai struktur Conveyor, sehingga diperlukan adanya kegiatan pengecekan secara berkala terhadap korosi agar dapat mencegah terjadinya korosi. Penelitian ini dilakukan pada struktur Conveyor yang terdiri dari 3 segmen dengan jumlah 27 Test point sepanjang 114 meter. Penelitian bertujuan untuk mengetahui jenis korosi, Pengendalian korosi, laju korosi dan sisa umur pakai pada struktur Conveyor. Metodologi dalam penelitian adalah pengukuran pengurangan ketebalan pada struktur Conveyor dengan alat Ultrasonic Thickness Gauge TT 130. Daerah penelitian memiliki kondisi lingkungan yaitu temperatur udara sekitar 26,7OC – 28,4OC, curah hujan sekitar 56,50 mm – 482,80 mm, dan kelembaban relatif dengan nilai tertinggi yaitu 89,3%. Jenis korosi yang terjadi pada struktur Conveyor adalah korosi merata. Metode pengendalian korosi menggunakan metode Coating dengan sistem Three layers. Metode Coating untuk Primer Coating menggunakan Seaguard 5000, Intermediate Coating menggunakan Sherglass FF, dan Top Coating menggunakan aliphatic acrylic modified polyurethane. Laju korosi struktur Conveyor berkisar antara 0,19 - 0,34 mm/tahun dan berdasarkan ketahanan korosi relatif baja termasuk ke dalam kategori good. Umur pakai struktur Conveyor 7 tahun dan sisa umur pakai berkisar antara 6,41 – 8,89 tahun. Sehingga terdapat 48,15% Test point yang tidak mencapai umur desain yaitu 15 tahun. Kata Kunci: Struktur Conveyor, Laju Korosi, Sisa Umur Pakai